T Wave Safety Margin during the Process of ICD Implantation As a Novel Predictor of T Wave Oversensing - Sun, Ya-Xun; Gao, Jing; Jiang, Chen-Yang; Xue, Yu-Mei; Xu, Yi-Zhou; Liu, Gang; Guo, Ji-Hong; Sheng, Xia; Ye, Yang; He, Hong; Zhao, Yun-Tao; Barajas-Martinez, Hector; et al. (Frontiers in Physiology, 2017)
Introduction: T wave oversensing (TWOS) is a major drawback of implantable cardioverter defibrillator (ICD) and data on predictors of TWOS in ICD is limited. We aimed to calculate a novel index of T wave safety margin (TWSM) and assess its potential for evaluating TWOS during the procedures of ICD implantation. Methods and Results: Thirty-two consecutive patients with ICD implantation were enrolled. During each procedure of ICD implantation, different ICD generators were connected to implanted sensing lead through active-fixation leads and bridging cables. R and T wave amplitudes were measured on ICD printouts according to the gain. The ICDs were programed to the most sensitive settings to reveal possible TWOS. A novel index TWSM was calculated according to the corresponding sensing algorithm of ICD. There was discrepancy of R wave amplitudes measured by different ICDs (P<0.01). In Fortify and Teligen ICDs, T wave amplitudes showed no difference (P>0.05) and TWSMs were sufficiently high (post sensing: 13.0±7.6 and 28.3±16.5, respectively, post pacing: 5.0±2.2 and 4.6±0.9, respectively). In 9 patients with 10 TWOS episodes detected during the procedure of ICD implantation, generators with the highest TWSM were chosen. Only one TWOS episode during pacing was recorded during the 25±7 mo follow-up period. Conclusions: We first propose the index of TWSM during ICD implantation as a potentially efficient predictor for TWOS. Evaluation of TWSM might help to reduce TWOS episodes in patients with high risk of TWOS. Prospective studies are warranted to validate this index and its potential to reduce TWOS episodes.